Analysis of Kaizen Implementation with Pareto Approach, Fishbone Diagram & Oee to Reduce Defects in Electronics Industry Assembly Production Line - Reza Kholil Yusni; Yunita Yunita; Muhammad Ibel; Asroni Asroni; Reno Agusto; Yudi Prastyo (INDO PUBLISHING, 2026)
The high defect rate in the assembly production line of the electronic manufacturing industry is a crucial problem that has an impact on reducing product quality and production efficiency. Based on company data, the defect rate in 2022 reached 12% with the dominant types of defects in the form of solder, bridging, missing components, and cold solder. This study aims to analyze the application of Kaizen as an effort for continuous improvement in reducing defects and increasing productivity. The methods used include Pareto analysis to determine the priority of problems, fishbone diagrams to identify the root cause of defects, and Overall Equipment Effectiveness (OEE) to evaluate the performance of the production system. The research data was obtained in the 2022–2025 period. The results show that the implementation of Kaizen is able to significantly reduce defects to 2% by 2025, increase production output from 400 to 700 units per day, and reduce downtime from 2 hours to 0.5 hours per day, with an OEE value of 71.4% which indicates an increase in production effectiveness. Thus, the application of Kaizen supported by the Pareto method, fishbone diagram, and OEE has proven to be effective in improving product quality and operational efficiency in a sustainable manner.